Correlation between arterial blood gas analysis and peripheral blood gas analysis in acid-base unbalance state - Hyun Lee Kim; Hyun Ho Ryu (The Korean Society of Nephrology, 2012)
Acid-base unbalance is most common problem in severe ill patient, especially in condition of abnormal renal function state. Acid-base unbalances are respiratory acidosis, respiratory alkalosis, metabolic acidosis, and metabolic alkalosis. Metabolic acidosis is frequently appeared in clinical state. Arterial blood gas analysis is considered as a basic test to the intensive care unit patient and emergency state. Recently some researches were done, comparing with arterial blood gas analysis and venous blood gas analysis. Because of venous blood sampling is safer than arterial blood gas analysis, and beside not so different among them for detecting pH, pCO2, HCO3, except pO2 measuring. This research was done in emergency room, and for explaining no different between arterial blood gas analysis and peripheral blood gas analysis result in acid-base unbalance state patient. Especially in kidney functions decreased state. : The study was done from March, 2010 to January, 2011. The object was 89 peoples who came to emergency room for treating internal medicine problem. (Women 53, average age: 66.7±12.1) Then compare between arterial blood gas analysis and peripheral blood gas analysis. Result: The mean arterial minus venous difference for pH, pCO2, and bicarbonate was −0.0170, 2.6528, and 0.6124. Bland-Altman plot was done for predicting agreement of two groups, and the scale was pH −2.95 to 4.17, pCO2 −4.45 to 9.76, bicarbonate −2.95 to 4.16, in 95% relative. Conclusion: The peripheral blood gas pH, pCO2, bicarbonate level is almost same as arterial blood gas analysis results. And enough to measuring acid-base unbalance state, in absent of arterial blood testing.